COVID-19 and the role of chronic inflammation in patients with obesity - Chiappetta, Sonja; Sharma, Arya M; Bottino, Vincenzo; Stier, Christine (International Journal of Obesity, 2020)
Coronavirus disease 2019 (COVID-19) and the risk of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) poses a particular risk to people living with preexisting conditions that impair immune response or amplify pro-inflammatory response. Low-grade chronic systemic inflammation, common in people with obesity, is associated with the development of atherosclerosis, type 2 diabetes, and hypertension, well known comorbidities that adversely affect the outcomes of patients with COVID-19. Risk stratification based on the Edmonton Obesity Staging System (EOSS), which classifies obesity based on the presence of medical, mental, and/or functional complications rather than on body mass index (BMI), has been shown to be a better predictor of all-cause mortality and it may well be that EOSS stages may better describe the risk of hyperinflammation in patients with COVID-19 infection. Analyzing a group of metabolic ill patients with obesity (EOSS 2 and 3), we found an increased interleukin-6 and linear regression analysis showed a positive correlation with C-reactive protein (CRP) (p = 0.014) and waist-to-hip-ratio (WHR) (p = 0.031). Physicians should be aware of these findings in patients with COVID-19 infection. Early identification of possible hyperinflammation could be fundamental and should guide decision making regarding hospitalization, early respiratory support, and therapy with immunosuppression to improve mortality.